Concept «Family»: Actualization in Russian, Danish and Finnish Media Discourses - V. V. Boguslavskaya; A. G. Chafonova (Дискурс)
Introduction. In the epoch of globalization and intercultural integration the content of the concept "Family" as a sociocultural value is the point of interest. Family is the universal value and one of the essential social institutions. The aim of the research is the linguocultural analysis of a complex concept «Family». Considering rapidly changing world trends the comparative linguosociocultural research of the concept "Family" appears to be highly relevant and important.Methodology and sources. The study of the present-day mediatexts of different linguistic communities (Russian, Danish and Finnish) is based on linguocultural analysis. The lexical item «family» (Dan. - "familie", Finn. - "perhe") is regarded as a key word. Online media of Russia, Danmark and Finland were chosen as the research resource. For research there were selected articles featuring the lexical item "family" allowing for any possible morphological changes, as well as the relevance of the content of the articles to the considered topics. All in all more than 300 articles from Russian online media "Vedomosti" and "Rossijskaja gazeta", Danish online media "Berlingske" and "Avisen.dk", Finnish online media "Helsingin Sanomat" and "Iltalehti" were analysed.Results and discussion. The analysis is based on the comparative study of linguistic representation of this concept in the Russian, Danish and Finnish mediatexts. The hypothesis was that the comparative intercultural research of a value-based concept use in different linguocultures may reveal in its linguistic representation not only sociocultural factors of its formation but ethnopsychological as well. Linguocultural analysis of the concept "Family" in the selected mediatexts was held on grammatical (morphosintactic) and lexical-semantic levels. As a result there were defined characteristics of the concept "Family" realisation in Russian and foreign media discourses.Conclusion. Comparative analysis of semantic realisation of a complex concept "Family" enables to reveal in linguistic features of its representation essential characteristics of the social background peculiar for modern Russian, Danish and Finnish societies.